Kerangka Hukum dan Tantangan Regulasi dalam Pengembangan E-Commerce di Indonesia: Analisis Kebijakan dan Implikasi Yuridis - Sembiring, Tamaulina Br.; Yolanda, Riska; Sitepu, Sofia Naliza; Siregar, Saskia Nabila; Putra, Raka Andika (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
Technological advances in the fields of transportation, communication, and information have accelerated globalization and triggered the rapid growth of electronic commerce (e-commerce). However, this development presents significant challenges in the national legal system, especially related to the application of corporate law in online transactions. This research aims to examine the legal framework and regulatory challenges in the development of e-commerce in Indonesia, highlighting the applicable policies and their juridical implications. The method used is a normative juridical approach with descriptive-analytical specifications, which allows the identification and analysis of legal norms contained in laws and regulations, legal doctrines, and relevant legal principles. Data are collected from primary, secondary, and tertiary legal materials, and then analyzed qualitatively through interpretation of existing legal substances. The results of the study show that the regulation of e-commerce in Indonesia has been accommodated through Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE), which was updated through Law Number 19 of 2016, as well as Law Number 7 of 2014 concerning Trade and Government Regulation Number 82 of 2012 concerning the Implementation of Electronic Systems and Transactions. However, obstacles are still found in its implementation, including weak electronic contract proof mechanisms, issues of trust and accountability, and low public understanding of digital transaction objects. This study recommends the drafting of a special law on e-commerce companies to strengthen legal certainty, consumer protection, and the sustainability of digital economy expansion in Indonesia.